Systematic review of return to work after mild traumatic brain injury: results of the International Collaboration on Mild Traumatic Brain Injury Prognosis - Cancelliere, Carol; Kristman, Vicki L; Cassidy, J David; Hincapié, Cesar A; Côté, Pierre; Boyle, Eleanor; Carroll, Linda J; Stålnacke, Britt-Marie; Nygren-de Boussard, Catharina; Borg, Jörgen (Archives of physical medicine and rehabilitation, 2014)
To synthesize the best available evidence on return to work (RTW) after mild traumatic brain injury (MTBI). MEDLINE and other databases were searched (2001-2012) with terms including "craniocerebral trauma" and "employment." Reference lists of eligible articles were also searched. Controlled trials and cohort and case-control studies were selected according to predefined criteria. Studies had to assess RTW or employment outcomes in at least 30 MTBI cases. Eligible studies were critically appraised using a modification of the Scottish Intercollegiate Guidelines Network criteria. Two reviewers independently reviewed and extracted data from accepted studies into evidence tables. Evidence was synthesized qualitatively according to modified Scottish Intercollegiate Guidelines Network criteria and prioritized according to design as exploratory or confirmatory. After 77,914 records were screened, 299 articles were found eligible and reviewed; 101 (34%) of these with a low risk of bias were accepted as scientifically admissible, and 4 of these had RTW or employment outcomes. This evidence is preliminary and suggests that most workers RTW within 3 to 6 months after MTBI; MTBI is not a significant risk factor for long-term work disability; and predictors of delayed RTW include a lower level of education (<11y of formal education), nausea or vomiting on hospital admission, extracranial injuries, severe head/bodily pain early after injury, and limited job independence and decision-making latitude. Our findings are based on preliminary evidence with varied patient characteristics and MTBI definitions, thus limiting firm conclusions. More well-designed studies are required to understand RTW and sustained employment after MTBI in the longer term (≥2y post-MTBI).